Metabolic Effects of Short-term GLP-1 Treatment in Insulin Resistant Heart Failure Patients - Nielsen, R.; Wiggers, H.; Halbirk, M.; Bøtker, H.; Holst, J. J.; Schmitz, O.; Frandsen, E.; Nielsen, S.; Møller, N.; Nørrelund, H. (Experimental and Clinical Endocrinology & Diabetes, 2012)
We studied the metabolic effects of 48-h GLP-1 treatment in insulin resistant heart failure patients.In a randomized placebo-controlled double-blinded cross-over study, 11 non-diabetic HF patients with IHD received 48-h GLP-1 and placebo-infusion. We applied OGTT, hyperinsulinemic clamp, indirect calorimetry, forearm, and tracer methods.7 insulin resistant HF (EF 28%±2) patients completed the protocol. GLP-1 decreased plasma glucose levels (p=0.048) and improved glucose tolerance. 4 patients had hypoglycemic events during GLP-1 vs. none during placebo. GLP-1 treatment tended to increase whole body protein turnover (p=0.08) but did not cause muscle wasting. No significant changes in circulating levels of insulin, glucagon, free fatty acids or insulin sensitivity were detected.GLP-1 treatment decreased glucose levels and increased glucose tolerance in insulin resistant HF patients with IHD. Hypoglycemia was common and may limit the use of GLP-1 in these patients. Insulin sensitivity, lipid-, and protein metabolism remained unchanged.Data were collected at the examinational laboratories of Department of Endocrinology and Department of Cardiology, Aarhus University Hospital, Aarhus, Denmark
Keywords: heart failure; insulin resistance; metabolism; incretines